Effect of Calorie or Exercise Labels on Menus on Calories and Macronutrients Ordered and Calories from Specific Foods in Hispanic Participants: A Randomized Study. Issue 8 (December 2016) - Shah, Meena; Bouza, Brooke; Adams-Huet, Beverley; Jaffery, Manall; Esposito, Phil; Dart, Lyn
The effect of menu labels on food choices is unknown in Hispanics. This study evaluated the impact of menu labels on calories and macronutrients ordered in Hispanics. 372 Hispanics (18–65 years) were randomly assigned to menus with no labels (NL) (n=127), rank-ordered calorie labels plus a statement on energy needs per meal (CL) (n=123), or rank-ordered exercise labels showing minutes of brisk walking necessary to burn the food calories (EL) (n=122). The menus had identical food choices. Participants were instructed to select foods from the assigned menu as if having lunch in a fast food restaurant. One-way analysis of variance found no difference in calories ordered (median (25th and 75th centiles)) by menu condition (NL: 785.0 (465.0, 1010.0) kcal; CL: 790.0 (510.0, 1020.0) kcal; EL: 752.5 (520.0, 1033.8) kcal; p=0.75). Calories from specific foods and macronutrient intake were not different by menu condition. Menu label use was 26.8% in the CL and 25.4% in the EL condition. Calories ordered were not different between those who used and those who did not use the labels. Regression analysis showed that perception of being overweight (p=0.02), selecting foods based on health value (p<0.0001), and meeting exercise guidelines (p<0.0001) were associated with fewer calories ordered. Logistic regression showed that selecting foods based on health value (p=0.01) was associated with higher food label use. Menu labels did not affect food choices in Hispanic participants. Future studies should determine if nutrition, exercise, and weight perception counseling prior to menu labels intervention would result in better food choices. Trial registration number: NCT02804503; post-results.